2015
DOI: 10.1016/j.nano.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology in bone tissue engineering

Abstract: Nanotechnology represents a major frontier with potential to significantly advance the field of bone tissue engineering. Current limitations in regenerative strategies include impaired cellular proliferation and differentiation, insufficient mechanical strength of scaffolds, and inadequate production of extrinsic factors necessary for efficient osteogenesis. Here we review several major areas of research in nanotechnology with potential implications in bone regeneration: 1) nanoparticle-based methods for deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
175
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(176 citation statements)
references
References 121 publications
(119 reference statements)
0
175
0
1
Order By: Relevance
“…[27][28][29] However, it has also been shown that certain scaffolds and signaling molecules can significantly increase survival of transplanted cells. 21,30,31 Levi et al observed that induced pluripotent stem cells exhibited a high degree of survival and acquired a fully differentiated osteogenic state when transplanted on a biomimetic scaffold into calvarial defects. 10 In general, we found that increased survival time of transplanted cells correlated with increased rates of healing in the calvarial defects.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] However, it has also been shown that certain scaffolds and signaling molecules can significantly increase survival of transplanted cells. 21,30,31 Levi et al observed that induced pluripotent stem cells exhibited a high degree of survival and acquired a fully differentiated osteogenic state when transplanted on a biomimetic scaffold into calvarial defects. 10 In general, we found that increased survival time of transplanted cells correlated with increased rates of healing in the calvarial defects.…”
Section: Discussionmentioning
confidence: 99%
“…La nanotecnología representa una frontera importante con potencial para avanzar significativamente en el campo de la ingeniería de tejidos [1,2]. La preparación y uso de membranas porosas basadas en nanofibras han cobrado interés recientemente para aplicaciones biomédicas, especialmente en la ingeniería de tejidos, cuyo objetivo es crear estructuras biodegradables y biocompatibles con propiedades mecánicas y biológicas similares a la matriz extracelular (ECM), entre varias técnicas de preparación de membranas porosas se presenta el electrohilado como una técnica con gran potencial [3].…”
Section: Introductionunclassified
“…Fibrous nanomaterials have been exploited in many biological applications, such as biosensing [56,57], drug delivery [58][59][60], bioseparation [61] and tissue engineering [62][63][64], thus opening new possibilities in the biomedical arena. As aforementioned, one of the most popular and versatile nanofibre fabrication techniques used for the production of synthetically or naturally--derived nanofibrous materials is electrospinning [38].…”
Section: Electrospinning Technology In Tissue Engineeringmentioning
confidence: 99%
“…Among other inorganic nanoparticulates, magnetic nanoparticles (MNPs) offer attractive possibilities in biomedicine and are more beneficial compared to microparticles, since they exhibit controllable size ranging from a few nanometers up to tens of nanometers, and dimensions smaller than or comparable to those of cells (10-100 μm), viruses (20-450 nm), proteins (5-50 nm) or genes (2 nm wide and 10-100 nm long) [97,98], improving tissular diffusion [99,100]. Moreover, therapeutic NPs with diameters ranging from 10-100 nm can be distributed throughout the circulatory system and penetrate small capillaries [62]. Surface modification provides additional functions rendering them ideal candidates as contrast enhancement agents in magnetic resonance imaging (MRI), in biomolecular detection, cell tracking, and for targeted drug delivery in tumor therapy [100,101].…”
Section: Electrospun Magnetoactive Nanocomposites In Tissue Engineeringmentioning
confidence: 99%